1999
DOI: 10.1093/jn/129.3.775s
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Therapy of Cancer by Dietary Monoterpenes

Abstract: Monoterpenes are nonnutritive dietary components found in the essential oils of citrus fruits and other plants. A number of these dietary monoterpenes have antitumor activity. For example, d-limonene, which comprises >90% of orange peel oil, has chemopreventive activity against rodent mammary, skin, liver, lung and forestomach cancers. Similarly, other dietary monoterpenes have chemopreventive activity against rat mammary, lung and forestomach cancers when fed during the initiation phase. In addition, perillyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
294
0
36

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(338 citation statements)
references
References 47 publications
8
294
0
36
Order By: Relevance
“…They are used as flavor additives in food, beverages, and perfumes. Recent studies have shown that monoterpenes exert antitumor activities, and suggest that these components can be a new class of chemotherapeutic agents (Elson and Yu 1994, Kellof et al 1996, Crowell 1999.…”
Section: Resultsmentioning
confidence: 99%
“…They are used as flavor additives in food, beverages, and perfumes. Recent studies have shown that monoterpenes exert antitumor activities, and suggest that these components can be a new class of chemotherapeutic agents (Elson and Yu 1994, Kellof et al 1996, Crowell 1999.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, limonene, the major Table 1. component (89.89%) found in the essential oil of Lithraea molleoides (Vell. ), although bereft of antimicrobial activity (17) has anti-carcinogenic activity (2) and can be used in medical dissolution of gallstones (6,10). The results of the analysis of the chemical composition of the essential oil of Lithraea molleoides (Vell.)…”
Section: Discussionmentioning
confidence: 99%
“…Beyond their desirable fragrances, some of these d-limonene oxygenated derivates, e.g. perillyl alcohol, carveol, carvone, geraniol and menthol, have shown biological activity in vivo against certain types of tumors, not only preventing the formation or progression of cancer, but also regressing the existing malignant tumors (8). These characteristics greatly enhance industrial interest in such compounds.…”
Section: Introductionmentioning
confidence: 99%